Nectarivorous Bird Emphysematous Ingluvitis (NBEI): A Novel Disease in Loriinae Birds Associated With Clostridium perfringens Infection - Rich, Andrew F.; Zendri, Flavia; Costa, Taiana; Timofte, Dorina; Drake, Gabby J.; Rowland, Hannah; Ashpole, Ian; Moore, Andrew; Chantrey, Julian (Frontiers in Veterinary Science, 2020)
A retrospective study revealed ten cases of emphysematous ingluvitis in Loriinae birds from two zoological collections between 2009 and 2020. Common clinical features were sudden death with gas distention of the crop, subcutaneous cervical emphysema and poor body condition, but also included collapse, hypothermia and abandonment. Macroscopic examination revealed moderate crop enlargement, distention and thickening with minimal intraluminal content, and moderate to severe submucosal to transmural gas-filled cysts (emphysema). Histopathology identified widespread transmural multifocal to coalescing empty pseudo-cystic cavities with lytic necrosis, pyo-/granulomatous inflammatory infiltrates, epithelial ulceration, parakeratotic hyperkeratosis, epithelial ballooning degeneration, and occasional intralesional rod-shaped bacteria. The lesion may have impaired the birds’ ability to ingest food, resulting in suboptimal body condition. Necrotizing to granulomatous aspiration pneumonia was also a feature in some cases. Anaerobic bacterial culture of four crops identified Clostridium perfringens with associated toxin genes for alpha and occasionally beta2 toxin (cpa and cpb2 genes respectively), by PCR analysis of bacterial isolates cultured from fresh or frozen tissue. C. perfringens was identified as the common etiological agent of emphysematous ingluvitis in crop and/or liver (six out of ten birds), and type A was confirmed in five birds. C. perfringens was not detected in the crop nor liver of two unaffected Loriinae birds. This is the first publication that characterizes nectarivorous bird emphysematous ingluvitis (NBEI), attributes C. perfringens as an etiological agent, and highlights this novel disease as an important cause of death in Loriinae birds, particularly in nestling and fledgling stage of development, but also in older lorikeets and lories.